Evaluation of the susceptibility to emamectin benzoate and lambda cyhalothrin in European populations of Cydia pomonella (L.) (Lepidoptera: Tortricidae). (July 2022) - Depalo, Laura; Pasqualini, Edison; Jan, Elias; Slater, Russell; Daum, Eve; Zimmer, Christoph T.; Masetti, Antonio
Abstract: The codling moth Cydia pomonella (L.) (Lepidoptera: Tortricidae) is one of the key pests of pome fruit and walnut in almost all growing regions of the world and has developed resistance to several insecticides. In this study, the susceptibilities of 15 codling moth populations to emamectin benzoate and 9 populations to lambda cyhalothrin collected in five European countries were measured by standard diet incorporation bioassays. Variation in susceptibility was observed among populations, with LC50 values ranging from 0.0017 to 0.0119 mg a.i./kg diet for emamectin benzoate and from 0.033 to 0.292 mg a.i./kg diet for lambda cyhalothrin. Our results revealed only small variations in emamectin benzoate susceptibility between populations, indicating no selection of resistance to this active ingredient. Even though a wider range of responses was detected for lambda cyhalothrin, our results also suggest that populations remain susceptible to this insecticide. Based on pooled LC95 evaluations, we propose the use of concentrations 0.02 mg a.i./kg of diet for emamectin benzoate and 0.60 mg a.i./kg of diet for lambda cyhalothrin in order to discriminate between resistant and susceptible individuals. Graphical abstract: The susceptibility of wild populations of the codling moth Cydia pomonella (L.) to emamectin benzoate and lambda-cyhalothrin, was tested by diet incorporation bioassays. Results revealed small variations in emamectin benzoate susceptibility between all the populations, while a wider range of responses was detected for lambda cyhalothrin. Image 1 Highlights: The susceptibility to two insecticides was tested in many codling moth populations. Small range of responses and no resistant strains were found for emamectin benzoate. A wider variability and a resistant population were detected for lambda cyhalothrin. 0.021 mg a.i./kg is suggested as discriminant concentration for emamectin benzoate. A discriminant concentration of 0.60 mg a.i./kg is proposed for lambda cyhalothrin.